Antimicrobial activity of Bothrops alternatus venom from the Northeast of Argentine - Bustillo, Soledad (2008)
Fil: Bustillo, Soledad. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.